SARS-CoV-2 Transmission Dynamics in Households With Children, Los Angeles, California - Tanaka, Melissa Lucero; Marentes Ruiz, Carolyn Jennifer; Malhotra, Sanchi; Turner, Lauren; Peralta, Ariana; Lee, Yesun; Jumarang, Jaycee; Perez, Stephanie E.; Navarro, Jocelyn; Dien Bard, Jennifer; Gordon, Aubree; Allen, E. Kaitlynn; et al. (Frontiers in Pediatrics, 2022)
Objectives: Studies of household transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) focused on households with children are limited. We investigated household secondary attack rate (SAR), transmission dynamics, and contributing factors in households with children. Materials and Methods: In this prospective case-ascertained study in Los Angeles County, California, all households members were enrolled if ≥1 member tested positive for SARS-CoV-2 by polymerase chain reaction (PCR). Nasopharyngeal PCRs, serology and symptom data were obtained over multiple visits. Results: A total of 489 individuals in 105 households were enrolled from June to December 2020. The majority (77.3%) reported a household annual income of <$50,000, and most (92.9%) were Hispanic/Latinx ethnicity. Children <18 years old accounted for 46.9% index cases, of whom 45.3% were asymptomatic. Household index cases were predominantly children during low community transmission and adults during the high community transmission period (𝝌2=7.647, p=0.0036. The mean household SAR was 77.0% (95% CI: 69.4-84.6%). Child and adult index cases both efficiently transmitted SARS-CoV-2 within households (81.9%, [95%CI: 72.1-91.9%] vs. 72.4% [95%CI: 59.8-85.1%], p=0.23). Household income and pets were significantly associated with higher SAR in the multivariable analysis of household factors (p= 0.0013 and 0.004, respectively). Conclusions: The SAR in households with children in an urban setting with a large ethnic minority population is much higher than previously described. Children play important roles as index cases. SAR was disproportionately impacted by household income. Vaccination and public health efforts need special focus on children and vulnerable communities to help mitigate SARS-CoV-2 spread.